Characterization of calmodulin binding domains in TRPV2 and TRPV5 C-tails - Holakovska, Blanka; Grycova, Lenka; Bily, Jan; Teisinger, Jan (Amino acids, 2011)
The transient receptor potential channels TRPV2 and TRPV5 belong to the vanilloid TRP subfamily. TRPV2 is highly similar to TRPV1 and shares many common properties with it. TRPV5 (and also its homolog TRPV6) is a rather distinct member of the TRPV subfamily. It is distant for being strictly Ca(2+)-selective and features quite different properties from the rest of the TRPV subfamily. It is known that TRP channels are regulated by calmodulin in a calcium-dependent manner. In our study we identified a calmodulin binding site on the C-termini of TRPV2 (654-683) and TRPV5 (587-616) corresponding to the consensus CaM binding motif 1-5-10. The R679 and K681 single mutants of TRPV2 caused a 50% decrease in binding affinity and a double mutation of K661/K664 of the same peptide lowered the binding affinity by up to 75%. A double mutation of R606/K607 and triple mutation of R594/R606/R610 in TRPV5 C-terminal peptide resulted in the total loss of binding affinity to calmodulin. These results demonstrate that the TRPV2 C-tail and TRPV5 C-tail contain calmodulin binding sites and that the basic residues are strongly involved in TRP channel binding to calmodulin.
Keywords: kalmodulin; Protein Binding; TRPV Cation Channels; sekvence aminokyselin; terciární struktura proteinů; vazba proteinů; molekulární sekvence - údaje; Amino Acid Sequence; Cell Membrane; Molecular Sequence Data; Protein Conformation; kationtové kanály TRPV; Protein Structure, Tertiary; konformace proteinů; Calmodulin; sekvenční seřazení; Sequence Alignment; buněčná membrána